Le Rêve d’un homme ridicule (Fedor Dostoïevski, 1877) adapté par Aleksandr Petrov (1992) : quand l’adaptation devient extrapolation poétique - Jacq, Jasmine (Slovo, 2019)
It was in 1992 that Aleksandr Petrov, a budding star in Russian animated film, directed The Dream of a Ridiculous Man, based on Dostoevsky’s short story of the same name, first published in 1877. Choosing this extremely complex work, which engages with all Dostoevsky’s views on religion, seemed to correspond to some deep inner need on the part of the filmmaker. The resulting work, a 20-minute short, is an extremely powerful narrative that testifies to the striking and almost uncanny affinity that exists between Dostoevsky & Petrov – a true meeting of minds. On the one hand Petrov throws himself into condensing and redeploying the original text, using various evocative means (such as noise, music, rhythm & colour) imbued with Dostoevsky’s narrative world. But above all it’s the element of fantasy and the central presence of the dream in the text that stands out, providing an ideal subject matter for a filmaker deeply inspired by the notions of slipping (from one reality to another), passages and metamorphoses. En 1992, Aleksandr Petrov, étoile montante de l’animation russe, réalisait Le Rêve d’un homme ridicule, d’après la nouvelle de Dostoïevski (1877). Le choix de cette oeuvre extrêmement complexe, sorte de synthèse de la pensée religieuse de Dostoïevski, paraît répondre à une nécessité intérieure pour le cinéaste. L’œuvre qui en ressort, court-métrage de vingt minutes, est un film d’une puissance narrative exceptionnelle, frappant par une communauté d’esprit et un niveau d’intimité troublants avec l’auteur. D’une part, Petrov s’adonne au nécessaire travail de condensation du texte, redéployé narrativement à travers différents procédés suggestifs profondément imprégnés de l’univers diégétique de Dostoïevski (bruitages, musique, rythme, couleurs...). Surtout, la dimension fantastique et la présence centrale du rêve dans le texte en font un matériau idéal pour un cinéaste très inspiré par les notions de glissement (d’une réalité à une autre), de passages et de métamorphoses. В 1992 году Александр Петров, восходящая звезда российского анимационного кинематографа, создаёт Сон смешного человека по одноимённому рассказу Ф.М. Достоевского (1877). Выбор этого крайне cложного произведения, некого синтеза религиозной мысли Достоевского, словно основан на внутренней потребности режиссёра. Получившаяся работа, двадцатиминутный короткометражный фильм, обладает невероятной повествовательной силой и поражает единением мысли и степенью близости с автором. С одной стороны, Петров выполняет необходимую работу по сжатию текста, который он изобразительно перестраивает через различные суггестивные приёмы (шумовое оформление, музыка, ритм, цвета...), глубоко пропитанные диегетическим миром Достоевского. С другой стороны, фантастический аспект и центральное место сна в тексте представляют идеальный материал для режиссёра, которого особо вдохновляют понятия перемещения (из одной реальности в другую), переходa и метаморфозы.